Impact of the COVID-19 Pandemic on Vaccine Hesitancy Towards Routine Childhood Immunizations in Kansas - Fields, Gregory (My University, 2025)
The COVID-19 pandemic was a devastating event causing loss of life, long-term illness, economic distress and daily disruptions beginning in early 2020. The consequences of this event are still evident in the medical community as there appears to be a resurgence in vaccine hesitancy for routine immunizations in children. The state of Kansas has shown a decline in routine childhood immunizations since the pandemic began leaving more children vulnerable to vaccine-preventable diseases. My applied practice experience was a project to better understand the challenges that immunizers in Kansas have been facing in recommending routine vaccines to children. By working under the advisement of Connie Satzler at EnVisage Consulting, Inc., Manhattan, KS, I developed seventeen questions to ask immunizers around the state of Kansas at in-person interviews to gain insight into what they are experiencing every day at the local level. After conducting thirty interviews, I determined that immunizers are facing more challenges now compared to before the pandemic began. Even though there appears to be fewer barriers to childhood vaccine availability, there has been an increase in the time it takes for immunization visits. Social media has caused confusion among parents on whether to vaccinate their children. More training would be beneficial for healthcare workers in tracking adherence rates, communicating with parents about vaccine hesitancy, and using social media as a tool to address misinformation. There is a sense of frustration among immunizers, and more collaboration would be useful to share ideas of what is working to increase acceptance of routine childhood immunizations from parents in Kansas.
Keywords: vaccine hesitancy; childhood immunizations; COVID-19 pandemic; immunization adherence; social media influence; thematic analysis